Oxidative coupling of methane to C-2 hydrocarbons on the Mg-Ti mixed oxide-supported catalysts at the lower reaction temperature: Role of surface oxygen atoms - Jeon, Wonjin; Lee, Jong Yeol; Lee, Maro; Choi, Jae-Wook; Ha, Jeong-Myeong; Suh, Dong Jin; Kim, Il Won (ELSEVIER, 2013)
The oxidative coupling of methane (OCM) couples methane molecules, which are the major components of natural gas, to form ethane and ethylene in order to produce fuels and chemicals. Because of the high reaction temperature (700-900 degrees C) to obtain high yields of desirable products, the OCM process has been difficult to commercialize. We have developed a less energy-intensive OCM process that exhibits higher activity at a lower reaction temperature using Mg-Ti mixed oxide-supported Na/W/Mn catalysts. The catalyst consisting of Mg/(Mg + Ti) = 0.5 (mol/mol) exhibited the highest C-2 hydrocarbons yields (i.e., 18.1% at 825 degrees C and 16.5% at 775 degrees C) among the mixed oxide-supported catalysts, which were higher than those of the conventional SiO2-supported catalyst particularly at a low temperature of 775 degrees C (12.8%). Based on catalyst characterization by transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), UV-vis spectroscopy (UV-vis), O-2-temperature programmed desorption (O-2-TPD), and CO2-temperature programmed desorption (CO2-TPD), the improved catalytic activity of the mixed oxide-supported catalysts was attributed to more active surface lattice O atoms. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: ALKALINE-EARTH; BASICITY; PERFORMANCE; GAS; MN/NA2WO4/SIO2; DIFFRACTION; ETHYLENE; NEUTRON; LA2O3; PRESSURE